Prevention and Control of Cervical Cancer by WHO-Endorsed Guidelines for Visual Inspection with Acetic Acid (Via) as a Simple Screening Method: Prevention and Control of Cervical Cancer - Ratyal, Sania; Saeed, Shazia; Hameed, Nasreen; Akram, Sara; Sabir Khan, Maryam; Fatima, Ayesha (Pakistan Journal of Health Sciences, 2024)
Despite the availability of primary prevention through Human Papillomavirus (HPV) vaccination, cervical cancer remains one of the leading causes of cancer-related deaths among women worldwide. And imposes an enormous global public health burden most notably for those living in low- or middle-income countries. Objective: To determine the diagnostic accuracy of VIA in diagnosing cervical cancer as compared to conventional methods. Methods: This retrospective study analyzed a cohort of women who underwent VIA screening for cervical cancer at Divisional Headquarters Teaching Hospital. The sample included 1,200 women aged 25-65 who had not been screened for cervical cancer in the previous three years. VIA screening followed WHO-recommended procedures, with presumptive diagnoses made through naked eye examination based on WHO guidelines for low-resource settings. Data was entered and analyzed by SPSS 25.0. Results: Among 1,200 women screened for cervical abnormalities using VIA, 280 tested positive (23.3%). The highest VIA-positive rates were in the 45-54 age group (112 positives), followed by the 35-44 group (70 positives). The diagnostic accuracy of VIA for cervical abnormalities shows high sensitivity (89.34%) and specificity (96.23%). VIA's positive predictive value was 85.83%, while the negative predictive value was 97.25%, indicating reliable detection of true positives and negatives. Conclusions: VIA was an accurate, affordable screening tool with a high level of sensitivity and specificity in detecting cervical precancerous lesions, particularly for low-resource settings. These results highlight the effectiveness of VIA screening across age groups, with higher detection rates in women over 35.